Cybernetic Aspects of Glottodidactic Processes (Selected Issues) - Szczodrowski, Marian (Glottodidactica, 2023)
A significant contribution to broadening and deepening the field of glottodidactics is made, inter alia, by the results of codematic and cybernetic research. Within the glottodidactic system, the following processes can be identified: 1) the encoding of information by the primary sender (the instructor), 2) the sending of information and its linguistic and extralinguistic monitoring to the primary receivers (learners), 3) the reception and decoding of information by the primary receivers, and the construction of matrices of new lexical and grammatical structures, 4) the encoding of information by the secondary sender (the learner), 5) the sending of information to the secondary receiver (the instructor) within a feedback system, 6) the reception of information by the second- ary receiver, its checking and correction, the regulation and syntactic ordering and renewal of the glottodidactic process.